Overview of Some Learning Methods for Early Childhood - Wahyuni, Vera Sri; Laksito, Grida Saktian (International Journal of Ethno-Sciences and Education Research, 2021)
Choosing a learning method in early childhood education is a method used by educators in carrying out learning activities for children to achieve certain competencies optimally. The purpose of this review of several learning methods in early childhood education is to obtain information about the growth and development that has been achieved by him during his education in learning in early childhood education. There are several lessons in early childhood education, and each method has its advantages and disadvantages. Based on the results of the discussion, it is known that each learning method in early childhood education has advantages and disadvantages. Therefore, educators in early childhood must be able to choose an appropriate method according to the goals, situations and conditions of their students.